Association between nasal and nasopharyngeal bacterial colonization in early life and eczema phenotypes. Issue 5 (6th April 2021) - Hu, Chen; Duijts, Liesbeth; van Meel, Evelien R.; Looman, Kirsten I. M.; Kiefte‐de Jong, Jessica C.; Pardo, Luba M.; Hijnen, DirkJan; Pasmans, Suzanne G. M. A.; de Jongste, Johan C.; Moll, Henriette A.; Nijsten, Tamar
Abstract: Background: An association has been reported between early life Staphylococcus aureus nasal carriage and higher risk of childhood eczema, but it is unclear whether this relationship is causal and associations with other bacterial species are unclear. Objective: To examine the associations of early life nasal and nasopharyngeal bacterial carriage with eczema phenotypes, and the direction of any associations identified. Methods: Among 996 subjects of a population‐based prospective cohort study, nasal swabs for Staphylococcus aureus, and nasopharyngeal swabs for Streptococcus pneumoniae, Moraxella catarrhalis and Haemophilus influenzae were collected and cultured from age 6 weeks to 6 years. Never, early, mid‐, late transient and persistent eczema phenotypes were identified from parental‐reported physician‐diagnosed eczema from age 6 months until 10 years. Multinomial regression models and cross‐lagged models were applied. Results: Staphylococcus aureus nasal carriage at 6 months was associated with an increased risk of early transient and persistent eczema (OR (95% CI): 2.69 (1.34, 5.39) and 4.17 (1.12, 15.51)). The associations between Staphylococcus aureus nasal carriage and eczema were mostly cross‐sectional, and not longitudinal. No associations of Staphylococcus pneumoniae, Moraxella catarrhalis and Haemophilus influenza nasopharyngeal bacterial carriage with eczema and eczema phenotypes were observed (OR range (95% CI): 0.71 (0.35, 1.44) to 1.77 (0.84, 3.73)). Conclusions: Early life Staphylococcus aureus nasal carriage, but not Staphylococcus pneumoniae, Moraxella catarrhalis and Haemophilus influenza nasopharyngeal carriage, was associated with early transient and persistent eczema. Staphylococcus aureus nasal carriage and eczema were mostly cross‐sectionally associated, and not longitudinally, making a causal relationship in either direction unlikely. Abstract : Early life Staphylococcus aureus nasal carriage was associated with an increased risk of early transient and persistent eczema. S. aureus nasal carriage and eczema were mostly cross‐sectionally associated, and not longitudinally, making a causal relationship in either direction unlikely. No associations of Streptococcus pneumoniae, Moraxella catarrhalis and Haemophilus influenza nasopharyngeal bacterial carriage with eczema and eczema phenotypes were observed.